Development of an Ultra-High Performance Liquid Chromatography Method for Simultaneous Determination of Six Active Compounds in Fructus aurantii and Rat Plasma and Its Application to a Comparative Pharmacokinetic Study in Rats Administered with Different Doses - Wenbo Wang; Linlin Zhao; Huiyong Huang; Jiamei Yao; Lu Zhou; Dongsheng Wang; Xinjian Qiu (Journal of Analytical Methods in Chemistry)
A rapid, accurate, and sensitive ultra-high performance liquid chromatography (UHPLC) method was established for simultaneously detecting naringin, hesperidin, neohesperidin, meranzin hydrate, naringenin, and hesperetin in Fructus aurantii (FA) decoction. Analysis was performed on Waters BEH (R) C18 (50 mm × 2.1 mm, 1.7 μm) at a flow rate of 0.2 mL/min by using (A) acetonitrile and (B) 0.5% acetic acid-water as the mobile phase. The method was well validated on linearity, precision, recoveries, and stability. Then, we used the same UHPLC conditions for quantitative analysis of meranzin hydrate, naringenin, and hesperetin in rat plasma. The method proved to be linear within the concentration ranges of 3.3–3300 ng/mL for meranzin hydrate, 6.95–3555 ng/mL for naringenin, and 1.8–236 ng/mL for hesperetin. The RSD of precision ranged from 1.22% to 9.08%, and the average extraction recovery ranged from 96.49 ± 1.42% to 102.01 ± 3.16%. Besides, we performed a comparative pharmacokinetic study after oral administration of FA decoction at a low dose of 15 g/kg and high dose of 30 g/kg body weight for seven days to rats. The AUC(0–t) and Cmax of meranzin hydrate, naringenin, and hesperetin were multiplied significantly with the increase of FA dosage, and the t1/2 of meranzin hydrate was faster than naringenin and hesperetin in the two groups.